Gereja Sehat: Kesehatian Sebagai Pemersatu Tubuh Kristus Berdasarkan Kisah Para Rasul 4:32 - Djone Georges Nicolas; Vroly Ruth Wowor; Natassa Sandriana; Herry Saragih; Pantas Butarbutar (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze health as a unifying Body of Christ as a healthy church based on Acts 4:32. The method used is qualitative exegesis and data collection through Bible sources, books, and journals that discuss topics as needed. The Church is usually a community of people whom God has justified function as God's representative on earth. Because, as a divine organism, love should be the basis of all forms of activities and goals of the Church as a sign that the Church is in good health and carrying out her responsibilities correctly and maximally. Only at this time, it is suspected that many churches are not showing signs of health, so they experience internal conflicts and eventually split. The result: a healthy church has unity in the community together among its congregations. In conclusion, the Church as a spiritual institution and belongs to God must be fit by showing the characteristics of oneness and unity within the assembly, so God's name is glorified.